2022
DOI: 10.3390/fishes7050273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Probiotics and Prebiotics on Growth, Physiological Condition, and Resistance to Pathogens Challenge in Nile Tilapia (Oreochromis niloticus)

Abstract: This study aimed to investigate the effects of the probiotic Betaplus® and prebiotic Technomos®as feed additives for Nile tilapia in terms of growth performance, health profiles, and resistance to infection with Aeromonas hydrophila and Pseudomonas fluorescens. A total of 960 healthy juvenile Nile tilapia (1.5 ± 0.01 g) were randomly divided into four experimental variants with three replicates for each variant. Fish were fed a commercial diet (control group, V0), supplemented with BetaPlus® probiotics–1%×BW (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Commercial probiotics can enhance weight gain, feed conversion ratio, and overall health status of fish. These findings emphasize the important role of probiotics in aquaculture by improving nutrient utilization and promoting better growth efficiency in fish (Sîrbu et al, 2022;Xia et al, 2020).…”
Section: Feed Conversion Ratiosupporting
confidence: 53%
“…Commercial probiotics can enhance weight gain, feed conversion ratio, and overall health status of fish. These findings emphasize the important role of probiotics in aquaculture by improving nutrient utilization and promoting better growth efficiency in fish (Sîrbu et al, 2022;Xia et al, 2020).…”
Section: Feed Conversion Ratiosupporting
confidence: 53%
“…Lysozyme activity is important in innate immunity, which is responsible for attacking and causing damage to the cell structures of invading bacteria (Saurabh and Sahoo, 2008). The lysozyme activity was found to increase in Nile tilapia (Oreochromis niloticus) fed with probiotic-or synbiotic-supplemented diets (Sırbu et al, 2022), Chinese drum (Miichthys miiuy) fed with live or dead cells of Clostridium butyrium CB2-supplemented diets (Pan et al, 2008), and red sea bream (Pagrus major) fed with b-glucan-supplemented diets (Dawood et al, 2017) but to remain unchanged in grouper (Epinephelus coioides) fed with Bacillus pumilus or B. clausii (Sun et al, 2010). However, our findings found that dietary A. niger supplement significantly decreased the lysozyme activity in shrimps, referring to that the probiotic showed negative effects on the activity of lysozyme in the innate immunity of shrimps.…”
Section: Sharma Et Al (2022) Indicated Thatmentioning
confidence: 99%
“…However, the application of antibiotics and chemotherapeutics in tilapia culture is strictly regulated due to their negative impacts, such as the development of antibiotic-resistant bacteria, immune suppression in the fish, and antibiotic residues [3]. Hence, the dietary supplementation of alternative, friendly prebiotics, probiotics, and immunostimulants, which help improve the immune responses of the fish and reduce disease susceptibility, is receiving increasing attention in aquaculture [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%